The SAMI Galaxy Survey: trends in [α/Fe] as a function of morphology and environment. Issue 1 (1st December 2021) - Watson, Peter J; Davies, Roger L; Brough, Sarah; Croom, Scott M; D'Eugenio, Francesco; Glazebrook, Karl; Groves, Brent; López-Sánchez, Ángel R; van de Sande, Jesse; Scott, Nicholas; Vaughan, Sam P; Walcher, Jakob; et al.
ABSTRACT: We present a new set of index-based measurements of [α/Fe] for a sample of 2093 galaxies in the SAMI Galaxy Survey. Following earlier work, we fit a global relation between [α/Fe] and the galaxy velocity dispersion σ for red sequence galaxies, [α /Fe]=(0.378± 0.009)log_10(σ /100)+(0.155± 0.003) . We observe a correlation between the residuals and the local environmental surface density, whereas no such relation exists for blue cloud galaxies. In the full sample, we find that elliptical galaxies in high-density environments are α-enhanced by up to 0.057 ± 0.014 dex at velocity dispersions σ < 100 km s −1, compared with those in low-density environments. This α-enhancement is morphology-dependent, with the offset decreasing along the Hubble sequence towards spirals, which have an offset of 0.019 ± 0.014 dex. At low velocity dispersion and controlling for morphology, we estimate that star formation in high-density environments is truncated ∼1 Gyr earlier than in low-density environments. For elliptical galaxies only, we find support for a parabolic relationship between [α/Fe] and σ, with an environmental α-enhancement of at least 0.03 dex. This suggests strong contributions from both environment and mass-based quenching mechanisms. However, there is no evidence for this behaviour in later morphological types.